2016
DOI: 10.1016/j.stem.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Nonhuman Primate Model of Severe Combined Immunodeficiency Using Highly Efficient Genome Editing

Abstract: Recent advances in genome editing have facilitated the generation of nonhuman primate (NHP) models, with potential to unmask the complex biology of human disease not revealed by rodent models. However, their broader use is hindered by the challenges associated with generation of adult NHP models as well as the cost of their production. Here, we describe the generation of a marmoset model of severe combined immunodeficiency (SCID). This study optimized zinc-finger nucleases (ZFNs) and transcription activator-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 52 publications
1
156
2
Order By: Relevance
“…In 2016, our research group focused on improving the efficiency of genome-editing technology in NHPs and reported the generation of immunodeficiency-related interleukin 2 receptor common gamma (IL2RG) KO marmosets using ZFN and TALEN [32]. In this study, we succeeded in the highly efficient generation of phenotypic individuals in the founder generation by carrying out detailed preliminary examinations using a genome editing tool.…”
Section: Target Gene Modification In Nhps Using Genome-editing Technomentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, our research group focused on improving the efficiency of genome-editing technology in NHPs and reported the generation of immunodeficiency-related interleukin 2 receptor common gamma (IL2RG) KO marmosets using ZFN and TALEN [32]. In this study, we succeeded in the highly efficient generation of phenotypic individuals in the founder generation by carrying out detailed preliminary examinations using a genome editing tool.…”
Section: Target Gene Modification In Nhps Using Genome-editing Technomentioning
confidence: 99%
“…To solve this problem, it is important to verify the genome editing tools in detail prior to producing NHP models. This point has been thoroughly studied in our research [32]. First, tools for use in genome editing in NHP embryos can be easily screened by evaluating genome modification activity in cultured cells (Fig.…”
Section: Reducing Mosaicismmentioning
confidence: 99%
“…Remarkable recent advances in genome editing technology have now made it possible to overcome these previous limitations (Sato et al 2016). Genome editing tools, i.e., engineered nucleases, bind to a target genome sequence and introduce specific double-strand breaks.…”
Section: Transgenic Techniques and Genome Editing Technology For Marmmentioning
confidence: 99%
“…Using these genome editing technologies, we recently generated X-linked SCID model marmosets by knock-out of interleukin-2 receptor subunit gamma gene (Sato et al, 2016). Currently, we are now seeking to generate marmoset models of autism spectrum disorders, including Rett syndrome (Chahrour and Zoghbi 2007;Kishi and Macklis 2005) and tuberous sclerosis complex (Ess 2010 ; Fig.…”
Section: Transgenic Techniques and Genome Editing Technology For Marmmentioning
confidence: 99%
“…Callithrix jacchus (common marmoset; CM) is a new world monkey (7), for which genome sequence analysis and transgenic animals have been established (8,9). We reported that CM possesses CD4T cells, CD8T cells and B cells in the similar ratio in PBMC and the T cells express CD25 and various cytokines after the activation, similarly to the cells of mouse and human (8).…”
Section: Introductionmentioning
confidence: 99%